Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Pada Toko Lagoena Bahan Kue Dan Plastik Marpoyan Pekanbaru - Dehotman, Khornelis (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This study aims to determine and analyze the factors that influence consumer satisfaction at the Lagoena cake and plastic material store in Marpoyan of Pekanbaru city. The population of this research is all consumers of the Lagoena Marpoyan Store in 2021 as many as 6,734 people. The research sample was taken from the entire population which was simplified by using the Slovin formula so that a sample of 99 people was obtained. Furthermore, respondents were taken a number of samples using accidental sampling. The research method used is descriptive and quantitative methods which are then analyzed using multiple linear regression methods. The results of research data processing show that the product variables (X1), price (X2), location (X3), people (X4), promotions (X5), process (X6) and consumer service(X7) simultaneously or together. the same has a positive and significant effect on consumer satisfaction at the Lagoena shop for cakes and plastics in Pekanbaru. The magnitude of the influence is 81.4% based on the results of the Adjusted R Square value of 0.814. As for the results of partial hypothesis testing, it can be obtained that the promotion variable (X5) has no effect on consumer satisfaction, while the other 6 X variables have a significant effect on consumer satisfaction